Advances in fiber‐based quartz enhanced photoacoustic spectroscopy for trace gas sensing - Feng, Wei; Qu, Yanchen; Gao, Yachen; Ma, Yufei (Microwave and optical technology letters, 2021)
Fiber‐based quartz enhanced photoacoustic spectroscopy (QEPAS) is a method for trace gas sensing with excellent properties such as high sensitivity and strong applicability. It has received extensive attention and become particularly attractive in recent years. Therefore, this invited paper analyzed and summarized the principle of its sensing as well as its technical characteristics. The latest research results, combed with the application mechanism and application fields of different types of QEPAS system, were introduced. Finally, its development trend was forecasted.